Mercado de la vivienda y el mecanismo de transmisión de la política monetaria: el caso peruano - Mayo Urtecho, Herbert Manuel (2022)
This thesis studies the monetary policy channel and its transmission in the Peruvian housing market. The role of financial and macroeconomic variables in the conduct of monetary policy is analyzed, in particular the role played by monetary policy in the boom in house prices since the beginning of the 21st century. As an analysis framework, it is carried out in the configuration of a small, neo-Keynesian open economy through DSGE models, estimated using Bayesian methods, which allows alternatively addressing the identification problem, characteristic of the monetary transmission channel.